2021
DOI: 10.1128/aem.00980-21
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Treatment before Chemical Disinfection Can Enhance Removal of Plastic-Surface-Associated Pseudomonas aeruginosa

Abstract: Opportunistic pathogens can linger on surfaces in hospital and building plumbing environments, leading to infections in at-risk populations. Further, biofilm-associated bacteria are protected from removal and inactivation protocols, such as disinfection. Bacteriophages show promise as tools to treat antibiotic resistant infections. As such, phages may also be useful in environmental applications to prevent newly acquired infections. In the current study, the potential of synergies between bacteriophage and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…Besides using mono phages, positive results have been reported on the use of phage cocktails to prevent ET colonization 18 by this bacterium. Outside the medical scope, effective use of mono phages or phage cocktails as biocontrol agents of PA in water 37 and phage combination with disinfectants to remove plastic-surface associated PA 38 have been recently reported. These studies highlight the urgent need to investigate new strategies to prevent, control, or remove PA biofilms from surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Besides using mono phages, positive results have been reported on the use of phage cocktails to prevent ET colonization 18 by this bacterium. Outside the medical scope, effective use of mono phages or phage cocktails as biocontrol agents of PA in water 37 and phage combination with disinfectants to remove plastic-surface associated PA 38 have been recently reported. These studies highlight the urgent need to investigate new strategies to prevent, control, or remove PA biofilms from surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of a bacteriophage cocktail was tested on the reference strain CR01 in comparison with the disinfectant Surfanios Premium (SP) (composed of N-(3-aminopropyl)-N-dodécylpropane-1,3-diamine and chlorure de didécyldiméthylammonium) (ANIOS, Lezennes, France). Both treatments were tested on dry spots and on pre-formed biofilms using a previously published method with some modifications ( Stachler et al., 2021 ). For bacteriophage cocktails preparation, the three bacteriophages were associated by diluting each of them in equal measure in either TSB or Phosphate Buffered Saline (PBS) (Thermo Fisher Scientific, Waltham, MA, USA) to obtain cocktails at three different final concentrations (3.10 4 PFU/mL, 3.10 6 PFU/mL or 3.10 8 PFU/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the therapeutic options mentioned above, several other phage-based alternative strategies have also been reported in preventing and controlling bacterial biofilms. A current study on the potential synergistic effect of phage and chemical disinfection against the opportunistic pathogen P. aeruginosa has shown that phages can effectively combine with chemical disinfectants, such as sodium hypochlorite and benzalkonium chloride, to improve the removal of wet biofilms and bacterial spots on surfaces and prevent the regeneration of dry biofilms at the same time [91]. In addition, He et al proposed a novel AIE-phage integrated strategy, in which phage PAP is equipped with photodynamic inactivation (PDI)-active AIEgens (luminogens with aggregation-induced emission property) to form a new type of antimicrobial bioconjugate, TVP-PAP, with a nearly 100% killing efficiency against multidrug-resistant P. aeruginosa [92].…”
Section: The Combination Of Phage With Other Strategiesmentioning
confidence: 99%